Metal Acetylides in Cycloaddition Reactions - Comas-Barceló, Júlia; Harrity, Joseph P. A. (Synthesis, 2017)
This review highlights recent advances in the synthesis of (hetero)aromatic systems via cycloaddition reactions of alkynylmetals with dienes and dipoles. This methodology is advantageous when accessing complex molecules because it offers a short, atom-economic, and regioselective route to quickly access scaffolds of broad interest to the chemical sciences.1 Introduction2 Synthesis and Applications of Metal Acetylides3 Use of Metal Acetylides in Cycloaddition Reactions3.1 The CuSAC Reaction3.2 The Kinugasa Coupling with Copper Acetylides3.3 Reactions of Pyrones and Aluminum Acetylides3.4 Direct Cycloadditions of Boron Acetylides4 Conclusion
Keywords: catalyst; alkyne; cycloaddition; aromatic; heterocycle